Pengaruh Latihan Dribbling With A Curving Line Trajectory Untuk Meningkatkan Keterampilan Dribbling Pemain Sepak Bola Ps. Undikam Mataram Tahun 2019 - Ismail Marzuki; Soemardiawan Soemardiawan (Lembaga Penelitian dan Pendidikan Mandala, 2019)
The focus of the problem in this research When competing frequently there are mistakes in dribbling, so from this it is necessary to have this exercise, to improve the dribbling skills of PS players. UNDIKMA Mataram. The purpose of this study is to determine whether there is an effect of Dribbling With A Curving Line Trajectory Exercise on the Dribbling Skills of PS Soccer Players. Mataram UNDIKMA 2019